The upper ocean structure of the Antarctic circumpolar current in the vicinity of the South-West Indian ridge - Gulekana, Mthuthuzeli Kenneth (Department of Oceanography, 2023)
A survey was undertaken in the southwest Indian sector of the Southern Ocean, at a fracture zone situated within the South-West Indian Ridge (SWIR). The fracture zone, formally called the Andrew Bain fracture zone (ABFZ), is centred at 50°S;30°E. The main focus of this investigation, which was strategically located around the ABFZ, was to study the dynamics and the structural modification of the Antarctic Circumpolar Current (ACC) when it encounters the complex SWIR. High sea surface variability has been observed at the southwest Indian sector of the Southern Ocean, specifically at and around 50°S;30°E. As the strong eastward flowing ACC encountered the elevated and complex bottom topography of the SWIR it was obstructed and deflected from its pathway and forced to flow through the ABFZ (50°S;30°E). Consequently the ACC was significantly narrowed at the fracture zone and immediately widened after it had flowed through the fracture zone. Its structure, therefore, was modified upstream of the ABFZ prior to entering the fracture zone, and was modified further downstream of the fracture zone. The fronts observed were the northern and southern branches of the Subantarctic Front, namely the northern Subantarctic Front (SAF), the southern Subantarctic Front (SSAF) and the Antarctic Polar Front (APF). Firstly, the SAF was occasionally encountered at the north of the survey grid, secondly, the SSAF was found to be highly variable with extreme meandering patterns across the survey grid; and lastly the APF which was observed along the 51 °S latitudinal band with minor northward and southward meanders. The SSAF and the APF partially converged at 50°30'S; 30°E, that is, at the position of the ABFZ. Coincidentally, at the same location, maximum surface geostrophic velocities of >25 cm/s were observed. The geostrophic velocities tended to be high at the vicinity of frontal bands, particularly at the convergence of the SSAF and the APF. The ACC was therefore, found to undergo structural modification, both zonally and meridionally, upstream and downstream of the ABFZ as a result of the constriction. Nutrients and dissolved oxygen (DO) had a defined distribution pattern: a decrease southwards and downwards within the survey grid. Maximum and minimum nutrients and DO were recorded south and north of the APF, respectively. Four water masses were encountered firstly the Subantarctic Surface Water (SASW), which was clearly defined north of the SSAF only upstream of the ABFZ, secondly the Antarctic Intermediate Water (AAIW) which was characterised by a salinity minimum (34.2), thirdly the Antarctic Surface Water (AASW) which was characterised by a temperature minimum of 2°C at 200m depth mainly located south of the APF in the Antarctic Zone (AAZ). Lastly, the Circumpolar Deep Water (CDW) which was the only present deep water due to the data limitations. The interaction and mixing between these water masses was evident particularly at the ABFZ. The circulation pattern of the ACC was observed to be controlled by the bottom topography. The conservation of vorticity generated latitudinal mesoscale meanders and cyclonic (cold) and anticyclonic (warm) eddies. Elevated surface velocities of >60 cm/s were observed at the ABFZ and at regions closer to the frontal bands.